Audiometric and vestibular outcomes following temporal bone fractures: a retrospective analysis of a major trauma center cohort in China - Wu, Caijuan; He, Qiang (Frontiers in Medicine, 2025)
BackgroundTemporal bone fractures form a major skull-base injury subset, yet prognostic data—drawn chiefly from short-term Western cohorts—remain sparse. This study therefore investigated long-term audiometric and vestibular outcomes by otic-capsule integrity to refine recovery estimates and treatment efficacy.MethodsWe conducted a retrospective cohort study of 1,871 adults with traumatic temporal bone fractures treated at a Level I trauma center in China (2014–2023). Patients were stratified by otic capsule status: sparing (OCS, n = 1,617) vs. violating (OCV, n = 254). Primary outcomes included pure tone audiometry and Dizziness Handicap Inventory scores assessed over 24 months. Statistical analysis employed mixed-effects models, Kaplan-Meier survival analysis, and propensity score matching. Two a priori hearing endpoints were used: “normal hearing” (PTA ≤25 dB HL) and “functional hearing recovery” (≥30 dB improvement from baseline).ResultsBaseline hearing impairment was significantly worse in OCV patients (84.6 ± 8.7 vs. 45.1 ± 8.5 dB HL, p < 0.001). At 24-month follow-up, functional hearing recovery (≥30 dB improvement) occurred in 90.4% of OCS patients, whereas 0% of OCV patients reached this threshold; return to normal hearing (PTA ≤25 dB HL) was observed in 38.5% of OCS patients and 0% of OCV patients. Multivariable analysis identified OCV fracture as the strongest predictor of severe hearing loss (OR 4.89, 95% CI: 3.42–6.99, p < 0.001). Complication rates were five-fold higher in OCV patients (31.5 vs. 6.1%, p < 0.001), including cerebrospinal fluid leak (13.8 vs. 2.0%) and meningitis (4.3 vs. 0.7%). Propensity-matched analysis demonstrated surgical benefit, with 7.6 dB hearing improvement compared to conservative management (p = 0.001).ConclusionsOtic capsule integrity represents the primary determinant of recovery following temporal bone fractures. OCV fractures demonstrate profound, persistent deficits with minimal recovery potential, while OCS fractures show excellent recovery prospects. These findings provide crucial prognostic information for patient counseling and treatment planning in temporal bone trauma management.